Can PhD programs from different areas be compared using bibliometric data? - Teixeira, António (2020)
The bibliometric indicators for the University of Aveiro PhD programs considering the 177 PhD students that finished their PhD in the civil year of 2016 have been obtained from SCOPUS and analyzed using principal component analysis and K-means cluster. The scientific production of those students distributed among 41 PhD programs has been used in this study, of which 38,4% were male and 61,6% were female. Moreover 18.6% of the PhD students have one supervisor, 63.3% have one supervisor and one co-supervisor while 18,1% have one supervisor and two co-supervisors. The PhD programs in the areas of social sciences, arts and humanities, services and education correlate less with Number of papers, Number of paper with international Institutions and Total citations than the PhD programs in the areas such as natural and exact sciences, health sciences and engineering.